Once upon a time essays in the philosophy of literature - Kivy, Peter (Rowman & Littlefield International, Ltd., 2019)
"Peter Kivy, world-renowned philosopher of art, completed work on this book shortly before his untimely death in 2017. In it he addresses the novel, making an invaluable contribution to the field of philosophy of literature and raising questions of a philosophical nature about the novel that will be of interest both to the professional philosopher and to the general reader"--